ICARE_08_12_026 ... : [Paysages, voyages, bateaux, divers] ... - inconnu], [Photographe (NAKALA - https://nakala.fr (Huma-Num - CNRS), 2021)
Groupe de personnes chassant le phoque sur la banquise [C. B (C. Bénard?)] ... : Source: CNRS, UMR CReAAH, Archives, ICARE_PV0812026 ...